HLTF and SHPRH are not essential for PCNA polyubiquitination, survival and somatic hypermutation: Existence of an alternative E3 ligase - Krijger, Peter H.L.; Lee, Kyoo-Young; Wit, Niek; van den Berk, Paul C.M.; Wu, Xiaoli; Roest, Henk P.; Maas, Alex; Ding, Hao; Hoeijmakers, Jan H.J.; Myung, Kyungjae; Jacobs, Heinz (DNA repair, 2011)
DNA damage tolerance is regulated at least in part at the level of proliferating cell nuclear antigen (PCNA) ubiquitination. Monoubiquitination (PCNA-Ub) at lysine residue 164 (K164) stimulates error-prone translesion synthesis (TLS), Rad5-dependent polyubiquitination (PCNA-Ub n) stimulates error-free template switching (TS). To generate high affinity antibodies by somatic hypermutation (SHM), B cells profit from error-prone TLS polymerases. Consistent with the role of PCNA-Ub in stimulating TLS, hypermutated B cells of PCNA K164R mutant mice display a defect in generating selective point mutations. Two Rad5 orthologs, HLTF and SHPRH have been identified as alternative E3 ligases generating PCNA-Ub n in mammals. As PCNA-Ub and PCNA-Ub n both make use of K164, error-free PCNA-Ub n-dependent TS may suppress error-prone PCNA-Ub-dependent TLS. To determine a regulatory role of Shprh and Hltf in SHM, we generated Shprh/ Hltf double mutant mice. Interestingly, while the formation of PCNA-Ub and PCNA-Ub n is prohibited in PCNA K164R MEFs, the formation of PCNA-Ub n is not abolished in Shprh/Hltf mutant MEFs. In line with these observations Shprh/Hltf double mutant B cells were not hypersensitive to DNA damage. Furthermore, SHM was normal in Shprh/Hltf mutant B cells. These data suggest the existence of an alternative E3 ligase in the generation of PCNA-Ub n.